Maroons and the Marooned : Runaways and Castaways in the Americas - Kelly, Joseph, 1962-; Bodek, Richard, 1961- (Book collections on Project MUSE., 2020)
"A provocative juxtaposition of escaped slaves and the shipwrecked across the Americas"--